Determination of Equilibrium Solubility and Octanol-Water Partition Coefficient of α-asaronol - Gong, Yitong; Zhang, Qunzheng; Zhou, Yuhao; Bai, Yajun; Zheng, Xiaohui (Scientific Journal of Technology, 2025)
Objective: The objective of this study was to ascertain the equilibrium solubility and oil-water partition coefficient (lgP) of α-fine-octanol in disparate media, thereby establishing a theoretical foundation for the examination of α-fine-octanol formulations and pharmaceuticals. Methods: The equilibrium solubility and oil-water partition coefficient of α-asaronol were measured using UV spectrophotometry and high-performance liquid chromatography (HPLC). The lgP of α-asaronol was determined using the shake flask method. Results: The equilibrium solubility of α-fine-octanol at 37°C in four aqueous media, namely, distilled water, saline, phosphate buffer solution (pH 6.8 PBS), and pH 7.4 PBS, was 6090.3, 5361.8, 6300.7, and 5260.3 μg/mL, respectively. The equilibrium solubility of α-fine-octanol in the oil-phase medium, soybean oil, was found to be 8225.4 μg/mL, which is greater than the equilibrium solubility of α-fine-octanol in the oil-phase medium, soybean oil, and the equilibrium solubility of α-fine-octanol in the oil-phase medium, soybean oil. Additionally, the octanol-water partition coefficient (lgP) of α-asaronol in these four aqueous media at 37°C ranged from 1 to 2. Conclusion: α-asaronol exhibits slight solubility in distilled water, physiological saline, pH 6.8 PBS, pH 7.4 PBS and soybean oil. It is a fat-soluble API with adequate water solubility and is classified as a highly transmissible drug. This characteristic renders it suitable for the development and utilization in the formulation of dosage forms intended for oral and rectal administration.